Kepemimpinan Non-Muslim dalam al-Qur’ān: Analisis terhadap Penafsiran FPI Mengenai Ayat Pemimpin Non-Muslim - Muhammad Suryadinata (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
This article analyses the interpretation belonging to the FPI organization on the leadership of non-Muslim in Islamic societies. Several Qur’ānic verses are used by FPI a center argument to refute non-Muslim to be a leader, as this refutation can be seen in Jakarta and other cities. FPI’s interpretation to ban non-Muslim as leader is looked textualist and coercive in manner. In fact, religion is not a determinant factor for indvidual’s work to totally work.